Peran Stres Kerja dan Kepuasan Kerja untuk Mengurangi Turnover Intention - Nazenin, Syarifah; Palupiningdyah, Palupiningdyah (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2014)
The purpose of this study conducted to examine the effect of work stress and job satisfaction on turnover intention of employee in production department. The sample was 86 respondent, using Slovin method with proportionate random sampling technique. The result showed that job stress has a positive effect on turnover intention while job satisfaction has a negative effect on turnover intention. This study conclude that job stress has positive and significant impact on employee turnover intention and job satisfaction significantly and negatively related to turnover intention of employees. Therefore, it is recommended to managerial level people to reduce stress levels in employees and to create a program for pressing turnover intention, such as promotional opportunities and improve employee rewards.